PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN DENGAN KEUNGGULAN BERSAING SEBAGAI VARIABEL INTERVENING PADA UKM DI KOTA AMBON - Senda Yunita Leatemia; Amelia Josefien Viotty Radianto; Franco Benony Limba; Theresia Febiengry Sitanala; Adonia Anita Batkunde (Media Bina Ilmiah, 2024)
Small and Medium Enterprises (SMEs) are the most important pillars of the Indonesian economy. Based on data from the Ministry of Cooperatives and SMEs, SMEs contribute 61.07% to GDP or IDR 8,573.89 trillion. The contribution of SMEs to the Indonesian economy includes the ability to absorb 97% of the total existing workforce and can collect up to 60.4% of total investment. However, the high number of SMEs in Indonesia cannot be separated from the existing challenges. To overcome existing challenges, this research uses the approach used in measuring and assessing intangible assets, namely intellectual capital. The research problem raised in this study is whether intellectual capital is proven to influence the financial performance of SMEs in Ambon City with competitive advantage as an intervening variable. The aim of the research is to obtain test results from the intellectual capital variable directly on the financial performance of SMEs in Ambon City and indirectly on the financial performance of SMEs in Ambon City through competitive advantage as an intervening variable. The results and outcomes achieved in this research are that the intellectual capital variable influences the financial performance of SMEs, while competitive advantage cannot mediate the relationship between intellectual capital and the financial performance of SMEs in Ambon City.